PENGELOLAAN KEUANGAN RUMAH TANGGA DALAM PERPEKTIF ISLAM - Husain, Hukmiah (PSW, 2011)
Money is not everything but many things that can not be done without money. Muslim households are built based on the intention of perfecting of worship, should not ignore the factors that often trigger the emergence of problems in the household of money.Management of household finances properly is a must for couples. Management includes how to obtain property / money, then sued the couple how to implement the financial management in meeting the needs of an increasingly complex manner that varied according to the financial condition of a family with a fixed reference to rules that do not conflict with Islamic values. That should be understood by married couples is how they communicate their family planning noted that financial management by taking into account the ratio of income and expenditure and keep documenting the movable and immovable assets. With the financial management of the slick, did not rule out the family can enjoy the tranquility of live that leads to my house my paradise.